The power of Natural Linguistics: Four levels of increasingly persuasive evidence for its superiority over other linguistic theories - Dressler, Wolfgang U. (Yearbook of the Poznan Linguistic Meeting, 2025)
This paper argues for the theoretical and explanatory superiority of Natural Linguistics (NatLing) over other linguistic models, presenting four ascending levels of evidence. The first level examines successful analyses of specific topics such as poetic occasionalisms, diminutives, and plural formation. The second level highlights innovative phenomena uniquely developed within NatLing, including phonotactics, morphosemantic transparency, and pragmatic variation in diminutives. The third level introduces novel subdisciplines—morphonotactics and morphopragmatics—demonstrating their wide empirical and theoretical impact across languages and acquisition studies. The highest level presents phenomena explainable only within NatLing, notably children’s strong blind-alley developments in morphology and syntax, which defy both generative and usage-based accounts. By integrating principles of iconicity, pragmatics, and self-organization, the paper concludes that Natural Linguistics provides the most comprehensive, cognitively grounded, and empirically productive framework for understanding linguistic structure, change, and acquisition.